Effect of phenobarbital on inducing insecticide tolerance and esterase changes in Aedes aegypti (Diptera: Culicidae) - Sousa-Polezzi, Rita de Cássia [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP] (Sociedade Brasileira de Genética, 2004)
The effect of phenobarbital (PB) on the induction of tolerance to the organophosphorous insecticide temephos (TE) was investigated in Aedes aegypti L4 larvae submitted to two different PB-treatments:(1) continuous treatment from the egg to the larval L4 stage and (2) discontinuous treatment in which L4 larvae were exposed for 30 h. Mosquitoes from two Brazilian cities were studied: São José do Rio Preto (SJ) in São Paulo State and Goiânia (GO) in Goiás State. According to criterions established by World Health Organization (WHO) mosquitoes from SJ are organophosphate-susceptible while mosquitoes from GO are organophosphate-resistant. For both SJ and GO larvae the two different PB-treatments resulted in significantly increased tolerance (measured by reduced mortality) to 0.01mg/L TE while for larvae exposed to 0.02 mg/L TE only continuous PB-treatment resulted in significantly increased TE-tolerance. The reduction of mortality rate was greater in SJ larvae than in GO larvae, confirming data from other organisms indicating that the effect of PB is more pronounced in susceptible strains. To test if oxidase enzymes were involved in PB-induced tolerance we treated PB-pretreated SJ and GO larvae with the oxidase inhibitor piperonyl butoxide (PBO) before exposure to TE and observed increased (rather than decreased) tolerance, suggesting that oxidases are not involved in the tolerance process and that PB and PBO can act in concert or synergistically. Esterase patterns of PB-pretreated larvae indicated that the cholinesterases EST-13 and EST-14 are involved in the PB-induced TE- tolerance, reinforcing a previous study carried out in our laboratory which suggested that increased esterase synthesis is the mechanism responsible for the development of insecticide resistance in Aedes aegypti.
Keywords: Aedes aegypti; insecticide resistance; phenobarbital; tolerance; pyperonyl butoxide; esterases